Use of Antiviral Prophylaxis in Influenza Outbreaks in Long Term Care Facilities - Allison McGeer; Daniel S Sitar; Susan E Tamblyn; Faron Kolbe; Pamela Orr; Fred Y Aoki (Canadian Journal of Infectious Diseases)
Influenza is a major cause of illness and death in residents of long term care facilities for the elderly, in part because residents' age and underlying illness increase the risk of serious complications, and in part because institutional living increases the risk of influenza outbreaks. The administration of antiviral medications active against influenza to persons exposed to influenza has been shown to protect them effectively from illness, and mass antiviral prophylaxis of residents is an effective means of terminating influenza A outbreaks in long term care facilities. The only antiviral currently licensed in Canada for influenza prophylaxis is amantadine, a medication active against influenza A but not influenza B. The National Advisory Committee on Immunization recommends that amantadine prophylaxis be offered to residents when influenza A outbreaks occur in long term care facilities. However, there remain a number of unanswered questions about how best to use amantadine for controlling influenza A outbreaks in long term care facilities. In addition, two members of a new class of antivirals called neuraminidase inhibitors have recently been licensed in Canada for the treatment of influenza, and are effective in prophylaxis. Issues in the use of amantadine in the control of outbreaks of influenza A in long term care facilities for the elderly are reviewed, and the potential uses of neuraminidase inhibitors in this setting are discussed.